Overcoming Saturation to Improve Student Learning Concentration Due to Online Learning - Dwitama, Andra Riyandi; Lubis, Hairani; Suhesty, Aulia (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
The Large-scale social restrictions in Samarinda due to the Covid-19 pandemic has caused learning and teaching activities to only be carried out online from their own homes. This limited learning method only through screens causes students to experience burnout in learning, to overcome this it is necessary to have high concentration of learning to stay focused on learning. This study aims to empirically test whether or not a correlation between learning concentration and burnout in high school students in Samarinda, which was designed to be a correlational test. By using simple random sampling technique, researchers obtained a sample of 156 high school students in Samarinda. Data was collected using measuring tools in the form of learning concentration scales and burnout scales which were analyzed using the Pearson Product Moment correlation test. From the research findings, it is known that there is a correlation between learning concentration and burnout in high school students in Samarinda. This conclusion is drawn based on the value of r count = -0.866 and p = 0.000 < 0.05. That is, the higher the concentration of learning possessed by students, the more burnout their learning will decrease.Adanya pembatasan sosial berskala besar di Kota Samarinda akibat pandemi Covid-19 menyebabkan kegiatan belajar dan mengajar hanya dapat dilakukan melalui online dari rumah masing-masing. Metode pembelajaran yang terbatas hanya melalui layar smartphone atau laptop ini menyebabkan siswa mengalami kejenuhan dalam belajar, untuk mengatasi hal tersebut maka perlu adanya konsentrasi belajar yang tinggi untuk tetap fokus mengikuti pembelajaran. Penelitian ini bertujuan untuk menguji secara empirik ada atau tidaknya hubungan antara konsentrasi belajar dengan kejenuhan pada siswa SMAN di Kota Samarinda, yang dirancang untuk uji korelasional. Dengan menggunakan teknik simple random sampling, peneliti mendapatkan sampel sejumlah 156 siswa SMAN di Kota Samarinda. Data dikumpulkan menggunakan alat ukur berupa skala konsentrasi belajar dan skala kejenuhan yang dianalisis menggunakan uji korelasi Pearson Product Moment. Dari temuan penelitian diketahui adanya hubungan antara konsentrasi belajar dengan kejenuhan pada siswa SMAN di Kota Samarinda. Kesimpulan tersebut ditarik berdasarkan besarnya nilai r hitung = -0.866 dan p = 0.000 < 0.05. Artinya, semakin tinggi konsentrasi belajar yang dimiliki oleh siswa, maka semakin kejenuhan belajarnya akan semakin menurun.